Literature Review: Terapi Komplementer Masase Menggunakan Minyak Esensial Lavender pada Remaja yang Mengalami Dismenorea Primer - Koernia Nanda Pratama (Journal of Bionursing, 2021)
Various complaints can occur during menstruation, one of which is dysmenorrhoea. Primary dysmenorrhoea is painless during menstruation without pathology, resulting from endometrium containing high amounts of prostaglandins. The estimated rate of dysmenorrhoea occurrence in adolescents 20% - 90%. About 15% of adolescents report severe menstrual pain. This can disrupt daily activities. High incidence of dysmenorrhoea is the reason not to go to school or college, few who seek treatment and only seek treatment independently. Medical intervention in primary dysmenorrhoea such as massage technique using lavender essential oil. Lavender as an essential oil has several benefits: reducing pain, antidepressants, and antimicrobials. Objective: The purpose of this study was to review some literature on massage using lavender essential oil to reduce the intensity of dysmenorrhoea pain in adolescents. Methods: Journal article searches are conducted electronically over the period 2008 - 2017, using multiple databases: Google Scholar, Sage, and ScienceDirect databases. Keywords used are "Primary dysmenorrhea / Dysmenorrhoea", "Lavender", and "Massage / Massage"; so get 3 articles to be reviewed. Results: Complementary nursing massage interventions using lavender essential oils can be categorized as safe and effective interventions in dealing with primary dysmenorrhoea. Discussion: The use of complementary nursing methods with a massage using lavender essential oil is effective in reducing primary dysmenorrhoea in adolescents. Complementary nursing methods with massage use should be further promoted and implemented as a treatment in primary dysmenorrhoea. Conclusion: The massage using lavender essential oil can reduce the intensity of pain in primary dysmenorrhoea.